Cyberspace and cybersecurity - Kostopoulos, George K. (CRC Press, Taylor & Francis Group, 2018)
Providing comprehensive coverage of cyberspace and cybersecurity, this textbook not only focuses on technologies but also explores human factors and organizational perspectives and emphasizes why asset identification should be the cornerstone of any information security strategy. Updates include topics such as cyber risks in mobile telephony, steganography, cybersecurity as an added value, ransomware defense, review of recent cyber laws, new types of cybercrime, plus new chapters on digital currencies and encryption key management.